Adiksimba sebagai Metode Berpikir Logis dalam Meningkatkan Kemampuan Menulis Ekspositoris Siswa - Deviana, Ria; Hidayati, Lutfiyah; Anifah, Lilik; Buditjahjanto, I Gusti Putu Asto (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
Writing exposition texts requires clear logic and argument structure, but many students still have difficulty organising ideas coherently due to their weak ability to build logical relationships between ideas. The purpose of this study is to examine the effectiveness of the ADIKSIMBA technique as a logical thinking development method in improving students' exposition text writing ability. Different from conventional methods that only emphasise text structure without guiding the thinking process, ADIKSIMBA offers a systematic thinking framework that helps students develop arguments gradually and logically. This study used a Classroom Action Research (PTK) approach consisting of 4 stages, namely planning, action, observation and reflection with the subject of 28 class X students at SMK Negeri 1 Surabaya. Data collection techniques were carried out through observation and interviews, as well as triangulation using analysis techniques consisting of data reduction, data presentation, verification and conclusion drawing. The results showed that the ADIKSIMBA technique effectively improved students' exposition writing skills logically, systematically and creatively, with an average score of 83.6 in cycle II. A total of 64.3% of students were in the high and very high categories, with the language quality aspect recording the highest score (88.1), followed by logical argument (84.3) and text structure (78.5). It can be concluded that ADIKSIMBA is a logical thinking strategy that can be used in improving students' ability to write coherent exposition texts.